Burnout in oral and maxillofacial surgeons in Brazilian population during the COVID-19 pandemic: a critical analysis (Research, Society and Development, 2022)
The training and activities of an oral and maxillofacial surgeon, although stimulating, motivating, and satisfactory, are not exempt from technical and psychological challenges. Residency training programs aim to develop necessary skills of resistance and rational decision-making under pressure in clinical, outpatient, and complex hospital interventions. Furthermore, these programs also require the fulfillment of activities outside the operating room, such as issuing diagnoses and planning high complexity procedures with a high risk of complications. The aim of this study was to evaluate the levels of burnout in attending surgeons and residents from oral and to maxillofacial surgery residency programs located in the State of Ceará, Brazil, during the SARS CoV-2 (COVID-19) disease pandemic. This observational, cross-sectional study with a quantitative approach was conducted on attending surgeons and residents registered at the Regional Council of Dentistry – Ceará Section. Data were obtained through an online questionnaire with three sets of questions: 1) professional factors; 2) the Oldenburg Burnout Inventory instrument; and 3) sociodemographic aspects. Quantitative data were analyzed with the Statistical Package for Social Science software. Nonparametric statistical analysis (Fisher and Kruskal-Wallis Exact tests) was used, in addition to the Chi-square test, adopting a significance level of 5%. A sample of 78 participants was obtained, in which most attendings (58.7%) and residents (40%) demonstrated moderate levels of burnout. We can conclude that the levels of burnout in oral and maxillofacial attending surgeons and residents from the State of Ceará during the COVID-19 pandemic were moderate, not resulting in high levels of emotional exhaustion and depersonalization.